2019
DOI: 10.1017/s1366728919000506
|View full text |Cite
|
Sign up to set email alerts
|

Changing expectations mediate adaptation in L2 production

Abstract: Native language (L1) processing draws on implicit expectations. An open question is whether non-native learners of a second language (L2) similarly draw on expectations, and whether these expectations are based on learners’ L1 or L2 knowledge. We approach this question by studying inverse preference effects on lexical encoding. L1 and L2 speakers of Spanish described motion events, while they were either primed to express path, manner, or neither. In line with other work, we find that L1 speakers adapted more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 89 publications
(185 reference statements)
5
28
0
Order By: Relevance
“…Our results indicate that AL frequency has no influence on the immediate AL-to-L1 priming, whereas L1 frequency appears to be an important factor. This idea is in line with experience-based accounts of L2 learning, which state that L2 learners transfer their L1 expectations to L2 during early phases of learning (e.g., Ellis, 2002; MacWhinney, 2008; Montero-Melis & Jaeger, 2019; Pajak, Fine, Kleinschmidt & Jaeger, 2016). Because L1 speakers of Dutch expect PO structures, they experience a prediction error when encountering a DO structure in the AL.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Our results indicate that AL frequency has no influence on the immediate AL-to-L1 priming, whereas L1 frequency appears to be an important factor. This idea is in line with experience-based accounts of L2 learning, which state that L2 learners transfer their L1 expectations to L2 during early phases of learning (e.g., Ellis, 2002; MacWhinney, 2008; Montero-Melis & Jaeger, 2019; Pajak, Fine, Kleinschmidt & Jaeger, 2016). Because L1 speakers of Dutch expect PO structures, they experience a prediction error when encountering a DO structure in the AL.…”
Section: Discussionsupporting
confidence: 66%
“…Similar to immediate priming, previous studies indicated that cumulative priming within L1 is sensitive to frequency effects; low frequency structures show larger cumulative priming effects than high frequency structures, when these structures appear frequently as a stimulus throughout the experiment (e.g., Fine, Jaeger, Farmer & Qian, 2013; Hartsuiker & Westenberg, 2000; Kaschak, Kutta & Jones, 2011). In addition, two recent studies showed that L1 inverse frequency effects can be transferred to L2 production as well (Kaan & Chun, 2018; Montero-Melis & Jaeger, 2019). The cumulative priming effect in our study seemed to be driven by AL frequency, although it is possible that L1 frequency plays a role as well, given that we have no data on the initial ditransitive preference of the participants in the study (note that there is no reason to assume that this preference would differ across groups).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptation to syntactic structure alternations (such as that between prepositional object and double object dative constructions in English) has been observed in L1 production (Jaeger & Snider, 2013;Kaschak & Borreggine, 2008;Kaschak, 2007;Kaschak et al, 2006Kaschak et al, , 2011, and in L1 comprehension (Farmer et al, 2014;Fine et al, 2013;Fine & Jaeger, 2016;Kaan & Chun, 2018b). Adaptation effects have also frequently been observed in L2 speakers (Jackson & Ruf, 2017;Kaan & Chun, 2018b;McDonough & Trofimovich, 2015;Montero-Melis & Jaeger, 2019;Shin & Christianson, 2012; see Jackson, 2018 for a review). The magnitude of these effects tends to be greater for less frequent structures (known as inverse probability effects).…”
Section: Structural Priming As a Learning Mechanismmentioning
confidence: 99%
“…On one hand, structural adaptation -an increased likelihood to use or expect the syntactic structures we are exposed to, persisting in the long term -is likely one of the mechanisms by which we tune into the patterns of our language (Peter & Rowland, 2019). There is evidence that prediction error drives adaptation to syntactic structure, both from computational modelling (Chang et al, 2006) and empirical studies with both first language (L1) and second language (L2) speakers (Fazekas et al, 2020;Montero-Melis & Jaeger, 2019). At the same time, evidence shows that violating expectations facilitates the formation of new individual declarative memories, too, including vocabulary learning (Greve et al, 2017;Stahl & Feigenson, 2017).…”
Section: Introductionmentioning
confidence: 99%